(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2024)
This article explores the comparison between traditional and modern approaches in English language teaching (ELT). It provides a comprehensive analysis of grammar-translation, direct, and audiolingual methods from traditional ELT, contrasted with communicative language teaching (CLT), task-based learning (TBL), and content-based instruction (CBI) from modern approaches. The discussion focuses on how each methodology meets the needs of learners in different contexts, highlighting the advantages and limitations of each approach.